Graphene oxide prevents mycobacteria entry into macrophages through extracellular entrapment. Issue 4 (29th January 2019) - De Maio, Flavio; Palmieri, Valentina; Salustri, Alessandro; Perini, Giordano; Sanguinetti, Maurizio; De Spirito, Marco; Delogu, Giovanni; Papi, Massimiliano
Abstract : GO trapping reduces mycobacteria entry in macrophages when the bacilli are in the external environment: a possible therapeutic strategy for tuberculosis. Abstract : Tuberculosis (TB) remains a global threat and there is an urgent need for improved drugs and treatments, particularly against the drug-resistant strains of Mycobacterium tuberculosis (Mtb). Graphene oxide (GO) is an innovative bi-dimensional nanomaterial that when administered in vivo accumulates in the lungs. Further, GO is readily degraded by peroxidases and has a high drug loading capacity and antibacterial properties. In this study, we first evaluated the GO anti-mycobacterial properties using Mycobacterium smegmatis (Ms) as a model. We observed that GO, when administered with the bacteria, was able to trap Ms in a dose-dependent manner, reducing entry of bacilli into macrophages. However, GO did not show any anti-mycobacterial activity when used to treat infected cells or when macrophages were pre-treated before infection. Similar results were obtained when the virulent Mtb strain was used, showing that GO was able to trap Mtb and prevent entry into microphages. These results indicate that GO can be a promising tool to design improved therapies against TB.